Early coupled up‐regulation of interleukin‐12 receptor beta‐1 in CD8+ central memory and effector T cells for better clinical outcomes in liver transplant recipients. (August 2015) - Uemoto, S.; Ozawa, K.; Kaido, T.; Mori, A.; Fujimoto, Y.; Ogawa, K.
Summary This study aimed to investigate the role of initial priming of interleukin (IL)‐12 receptor beta‐1 in CD8+central memory T cells (initial IL‐12RTCM priming) and CCR7‐negative subsets (CNS) in effector cell expansion and clinical outcome after living donor liver transplantation (LDLT). One hundred and six patients who underwent LDLT were classified into the following three groups according to hierarchical clustering of CD8+CD45 isoforms before LDLT: I, naive‐dominant; II, effector memory‐dominant; and III, effector‐dominant. The pre‐existing CD8+effector cells (TE) and activated immune status increased progressively from group I to group II to group III. Groups I, II and III received tacrolimus (Tac)/glucocorticoid (GC) regimens. Eighteen group III recipients received Tac/mycophenolate mofetil (MMF) and were defined as group IV. Initial IL‐12RTCM priming was slightly, moderately and markedly decreased in droups I, II, and III, respectively. Initial priming of IL‐12Rβ1 in CNS was decreased markedly in the three groups with marked decreases of TE, perforin and interferon (IFN)‐γ; all parameters were restored by up‐regulation of IL‐12Rβ1+TCM through the self‐renewal of TCM. The lag time required until coupled up‐regulation of IL‐12Rβ1 of TCM and CNS to above baseline was 12, 20 and 32 days in groups I, II and III, respectively. Inferior clinical outcomes were associated with increasing lag time. In contrast, the initial priming of IL‐12Rβ1 in TCM and CNS remained above baseline in group IV due to MMF‐mediated increase of IL‐12Rβ1. Early coupled up‐regulation of TCM and CNS leads to efficient TE differentiation and optimal clinical outcomes.